The war from the death of Lord Raglan to the evacuation of the Crimea - Russell, William Howard Sir 1820-1907 (Cambridge University Press, 2013)
During the Crimean War, the pioneering reports of the journalist William Howard Russell (1820-1907) shaped public opinion, helped bring down a government, and inspired the work of Florence Nightingale. This second volume of dispatches, published in 1856, concludes with poignant reflections on the memorials to the fallen